LOCAL COMMUNITY PERCEPTION ABOUT THE PLANNING AND DEVELOPMENT OF TOURISM DESTINATIONS IN KEPULAUAN SERIBU REGENCY JAKARTA - Fahrurozy Darmawan (Jurnal Infrastruktur, 2022)
Kepulauan Seribu Administrative Regency, which one of the National Tourism Destinations, continues to transform into a leading tourist area in Indonesia. The development of tourism in this area also has an impact on social and economic life. Planning and developing tourism that does not place the local community as the main actor also affects the understanding of the community. This study tries to identify the local community's perception of the planning and development of Priority Tourism Destinations in the Thousand Islands Regency, DKI Jakarta and the socio-cultural impact of tourism in the area. This study uses data collection techniques through observations at the destination and explores the informants and resource persons. The study results found that public understanding of tourism planning and development in the Thousand Islands Regency is still lacking. This problems arises due to a lack of communication between stakeholders, both central/regional government, private sector and local communities..